MODERN THEORIES OF LEADERSHIP IN THE CONTEXT OF DEVELOPING THE COMPETENCIES OF A PROJECT MANAGER (Development Service Industry Management, 2025)
The article discusses the integration of modern leadership theories into the system of forming project manager competencies, taking into account methodological approaches to project management. The authors note that in conditions of dynamic change, project management is becoming one of the key tools for organizational adaptation, and the success of the team and the effectiveness of achieving goals increasingly depend on the leadership («energy») skills of the project manager. In today's world, a project leader not only coordinates processes but also acts as an agent of innovation and a moderator of an organizational culture focused on flexibility, learning, and creativity.Next, the evolution of leadership theories was analyzed – from personality-oriented, situational, behavioral, and transformational to interpersonal and contextual – and the influence of modern approaches to leadership on the formation of project manager competencies was determined. It is argued that an effective project manager must combine personal leadership qualities with the social role of a facilitator of team processes, adapting their management style to the chosen methodology, project context, and personality of the project manager. In addition, the IPMA ICB4 individual competency assessment system and PMBoK standard competencies are considered, and the results of a survey of Ukrainian project managers on the identification of key leadership qualities that determine project success are analyzed. Particular attention is paid to analyzing the relationship between project manager positions and the set of necessary skills in accordance with the components of the talent triangle from the Project Management Institute.The results of the study emphasize that a modern project manager should act not only as a process administrator, but also as a driver of change, a facilitator of team interaction, and a cultivator of a culture of trust and responsibility, capable of delegating and developing the internal leadership of team members. The type of project management methodology (Waterfall, Agile, Hybrid) determines the dominance of certain leadership styles: directive, facilitative, or adaptive. Flexibility in choosing a leadership style is critical to successful project implementation. Integrating these concepts into the competency model of project management will help prepare a new generation of leaders capable of working in flexible, digital, and multicultural environments.
Keywords: leadership; project management; project manager; competencies; project management methodologies